Effect Addition of Different Probiotic in Aquaponic Systems Towards The Growth Rate and Survival Rate of Catfish (Clarias sp.) - Ayu Herdianti Primashita; Boedi Setya Rahardja; Prayogo . (Journal of Aquaculture Science, 2017)
Catfish (Clarias sp.) is a freshwater fish that is widely cultivated because it is a leading commodity. Increased production of catfish resulted in extra area of cultivated land and water use. The technology suitable to be applied is aquaponic system. In addition to saving land and water use, Aquaponic is also improving business efficiency through the utilization of nutrients from food remains and fish metabolism. Water quality is an important factor for the success of cultivation. Maintenance catfish with the addition of probiotics in aquaponic system can be a solution for maintaining water quality, because it contains bacteria that can increase nitrite to nitrate changes that can be utilized for growth of plants and do not poison the fish. The purpose of this study was to determine the effect of different probiotics in the aquaponic system towards growth rate and survival rate of catfish. The method that used in this research is experimental with completely randomized design (four  treat and five repeated) are P0 (control), P1 (probiotic A), P2 (probiotic B) and P3 (probiotic C). Analysis of data processed using Analysis of Variance. If there are significant differences then continued Duncan's Multiple Range Test. The results showed that the giving of probiotics in the aquaponic system is significantly different (p <0.05). The final conclusion is that the addition of probiotics in  aquaponic system affect the growth rate and survival rate of catfish. The highest specific growth rate (0.025%/ day) and the highest survival rate (77.8%) contained in the P2 treatment. The lowest specific growth rate (0.019% /day) and the lowest survival rate (64.4%) contained in P0 treatment (control).   Keywords : Aquaponic, Catfish, Probiotic, Growth Rate, Survival Rate, Clarias sp.